RELEVANCE OF CHANGES IN THE INDEPENDENT CURRICULUM TO STUDENT ACHIEVEMENT - Nasution, Putra Thoip; Lubis, Jamaliyah Hasan (EXCELLENCE: Journal of English and English Education, 2023)
The emergence of the coronavirus in various parts of the world raises new challenges in the world of education that demand changes in the learning system. In the process of restoring education in Indonesia, the government is making efforts in the form of launching a new program, namely the Independent Curriculum. Curriculum changes in Indonesia certainly have an impact on the world of education, especially on student achievement. This study used a qualitative approach with a descriptive research type. The data collection technique used is a collection of concepts. The results of this study indicate that curriculum changes have a significant effect on student achievement.